Genetic polymorphisms of toll-like receptors in leprosy patients from southern Brazil - Masin, Priscila Saamara; Visentin, Hugo Alves; Elpidio, Laíse Nayana Sala; Sell, Ana Maria; Visentainer, Lorena; Lima Neto, Quirino Alves De; Zacarias, Joana Maira Valentini; Couceiro, Patrícia; Higa Shinzato, Andressa; Santos Rosa, Manuel; Rodrigues-Santos, Paulo; Visentainer, Jeane Eliete Laguila (Frontiers in Genetics, 2022)
Leprosy is a chronic disease, and it is a global health issue, with a high number of new cases per year. Toll-like receptors can respond to mycobacterial molecules in the early stage of infection. As important components of the innate immune response, alterations in genes coding for these receptors may contribute to susceptibility/protection against diseases. In this context we used a case-control study model (183 leprosy cases vs. 185 controls) to investigate whether leprosy patients and the control group, in southern Brazil, have different frequencies in TLR1 (TLR1 G>T; rs5743618), TLR2 (TLR2 T>C, rs1816702 and rs4696483) and TLR4 (TLR4 A>G, rs1927911) polymorphisms. Analysis of the TLR1 1805G>T polymorphism presented the G/G genotype more frequently in the control group. TLR2 T>C rs1816702 and TLR2 T>C rs4696483, the T/T and C/T genotype, respectively, were more frequent in the control group compared to leprosy patients, suggesting protection from leprosy when the T allele is present. Haplotype analyses between TLR1 (rs5743618) and TLR2 (rs1816702 and rs4696483) polymorphisms suggest risk for the presence of TCC haplotype and protection in presence of TCT haplotype. This study suggests that polymorphisms in TLR1 and TLR2 are factors that may contribute to the development/resistance of leprosy.